Das frühste Amduat-Exemplar im Tal der Könige: Die neu gefundenen Gipsputz-Fragmente im Grab Thutmosis I. (KV 38) - Ghany, Khaled Abdel (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
After G. Daressy had indicated in the Catalogue général that two small mud-plaster fragments of Amduat (CG 24990 C) were found in the tomb of king Thutmosis I (KV 38), egyptologists assumed that the tomb KV 38 may have been originally decorated with a mud-plaster version of Amduat – however, there were neither archaeological evidences nor illustrations available. For this reason in 2015 I started an exploration in the tomb KV 38. In this search, I actually found further mud-plaster fragments of the Amduat book in the small side chamber (Ja). After examination and analysis of the discovered fragments with comparable scenes from the tomb of Thutmose III (KV 34) I think that the mud-plaster fragment scenes from the tomb of Thutmosis I (KV 38) are much earlier than the similar scenes from the tomb of Thutmosis III. Therefore, the discovered mud-plaster Amduat fragments from the tomb KV 38 represent the earliest ever Amduat specimen in the Valley of the Kings, made by the King Thutmosis I.